A Real-world Patient Registry for Oritavancin Demonstrates Efficacy and Safety Consistent With the Phase 3 SOLO Program. (19th March 2018) - Redell, Mark; Moeck, Greg; Lucasti, Christopher; Durso, Stephanie; Kennedy, Cynthia; Fusaro, Karen; Loutit, Jeff; Dudley, Michael
Abstract: Background: Oritavancin is a lipoglycopeptide used in the treatment of acute bacterial skin and skin structure infections (ABSSSIs) in adults. To characterize its use in patients in the postapproval setting, a patient registry was developed. Methods: Data collected in an ongoing retrospective observational registry are used to evaluate the utilization, outcomes, and adverse events (AEs) associated with oritavancin for the treatment of infections presumed or confirmed to be caused by gram-positive (GP) bacteria in clinical practice. Results: Data for 112 patients from 8 sites were collected. All patients received a single 1200-mg dose of oritavancin mostly in an infusion center. Infection type included cellulitis (67.0%), cutaneous abscess (21.4%), and wound (4.5%). Most patients (72.3%) received 1 or more antimicrobial agents for the index GP infection within 28 days prior to oritavancin treatment. Of positive cultures obtained prior to oritavancin administration, methicillin-resistant Staphylococcus aureus was the predominant pathogen (78.4%). A positive clinical response was observed in 92.8% of patients, and microbial eradication was observed in 90.0% of patients with post-therapy cultures. Within 28 days following oritavancin administration, 4 (3.6%) patients were hospitalized for failure of treatment of the index infection. Five (4.5%) patients experienced 1 or more possible drug-related AEs, which were consistent with types previously reported. There were no drug-related serious AEs reported. Conclusions: Clinical and microbiologic outcomes and safety of single-dose oritavancin 1200 mg were similar in this older patient population with multiple comorbid conditions to those observed in the phase 3 SOLO trials.